Website Design Computer Stores Anugerah Jaya Using PHP - Budi Sulistiyo; Cut Asiana Gemawaty (Jurnal Sistem Informasi, 2006)
One use of the web in the business world today is as means for introducing a company and their products generate, publications and promotional activities are needed for development their efforts to be more recognized by the public. Sale and purchase of computer equipment and accessories is a growing business today needs community will encourage business computing devices is becoming ever developed. One of the facilities used for the promotion of alternative marketing the products sold are to design and make a website and register to the website so that it can be accessed by Internet users anywhere, anytime.Therefore, using PHP scripts in designing and making dynamic website, website management is expected to become easier and process of updating the displayed data can be done.